Dandangan: Tradisi Menyambut Bulan Ramadan Masyarakat Kudus dalam Perspektif Hadis dan Psikologi - Friyadi, Arif; Abdillah, Aufa (JASNA : Journal For Aswaja Studies, 2023)
AbstractThe Dandangan tradition is a tradition that has existed since the time of the Sunan Kudus to welcome the arrival of the holy month of Ramadan. The Dandangan tradition in Kudus is still preserved every year. Unfortunately, this tradition had to be tainted by some non-moderate religious figures by accusing the implementation of this tradition of heresy. The purpose of this study is to find out the history of the Dandangan tradition in Kudus as a living hadith to welcome the holy month of Ramadan. This research uses a qualitative research method with an ethnographic approach. Data is collected through literature review, observation, and in-depth observation. The data were analyzed using functional structural proximity. The results showed that the existence of Islam is an inseparable part of the Kudus community so the implementation of welcoming the holy month of Ramadan alone has become a tradition of the Kudus community known as the Dandangan tradition. The function of this tradition is nothing but an expression of gratitude for the arrival of the holy month of Ramadan and a means of social interaction that increases the homogeneity of the Kudus community in one social identity.Keywords: Tradition, Ramadan, Hadith.Â AbstrakTradisi Dandangan merupakan tradisi yang sudah ada sejak zaman Sunan Kudus untuk menyambut datangnya bulan suci Ramadan. Tradisi Dandangan di Kota Kudus masih dilestarikan dalam setiap tahunnya. Sayangnya tradisi ini harus dinodai oleh beberapa tokoh agama yang tidak moderat dengan menuduh pelaksanaan tradisi ini sebagai bidâ€™ah. Tujuan dari penelitian ini adalah untuk mengetahui sejarah dari tradisi Dandangan di Kota Kudus sebagai living hadis menyambut bulan suci Ramadan. Peneletian ini menggunakan motede penelitian kualitatif yang dengan pendekatan etnografi. Data dikumpulkan melalui telaah data pustaka, observasi, pengamatan mendalam. Data dianalisis dengan menggunakan pedekatan struktural fungsional. Hasil Penelitian menunjukkan bahwa keberadaan agama Islam menjadi bagian yang tidak terpisahkan pada masyarakat Kudus sehingga pelaksaan menyambut bulan suci Ramadan saja telah menjadi tradisi masyarakat Kudus yang dikenal sebagai tradisi Dandangan. Fungsi dari pelaksaan tradisi ini tidak lain adalah ungkapan syukur atas datangnya bulan suci ramadan serta menjadi sarana interaksi sosial yang meningkatkan homogenitas masyarakat Kudus dalam satu identitas sosial.Kata kunci: Tradisi, Ramadan, Hadis.